Garden to Table: A Head Start Adventure - Cunningham, Alissa (My University, 2021)
Every summer I work solo in my position as a chef supervisor for the Northland Head Start. Classes are reduced from ten rooms and a maximum of 170 students to two rooms and a maximum of 34 students. Head Start is a program that prepares children ranging from infant to pre-school age to enter school, and specifically serves low-income families. The Northland Head Start is host to children that are three to five years old. Upon returning from several months of a shut-down in March 2020, due to Covid, classes were able to safely resume in July of 2020. Class sizes were limited, and social distancing was enforced. I began to brainstorm how I could help brighten the days of these kids who were experiencing a whole new norm. Additionally, I saw the need for healthy eating education. These were the days of produce boxes being placed into trunks as the world tried to figure out how to help mass amounts of people who were unemployed or struggling to feed their families. I remembered a small bag-style garden on folding legs that the teachers had tried to use a few years before. I dug it out of storage and utilized my neighborhood social media platform to ask for donations of soil. I set it up in the playground and used seeds I had on hand as well as those donated from fellow staff members. We were quickly rewarded with lettuce and basil that were used in school lunches, and later a few rainbow carrots that were passed around for exploration. I witnessed the pure eagerness of the children seeing the tiny plants emerge from the soil and then trying the end product. That is when I knew I had to do something bigger. I began to research raised garden beds that would be suitable for our playground, along with a source for soil and water. My goal for this project was to see if I could increase vegetable consumption in the classroom during meals. I also wanted to increase awareness of the garden system and to see if it could serve as a learning medium.